2022
DOI: 10.1093/infdis/jiac024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Between-Individual Variability in Plasma Clearance of Bedaquiline and Clofazimine in South Africa

Abstract: Objective Plasma bedaquiline clearance is reportedly more rapid with African ancestry. We examined whether genetic polymorphisms explained between-individual variability in plasma clearance of bedaquiline, its M2 metabolite, and clofazimine in a cohort of patients treated for drug-resistant tuberculosis in South Africa. Methods Plasma clearance was estimated with non-linear mixed-effects modelling. Associations between pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Black race was much more prevalent in the PROBeX study compared with the phase II studies (82% vs 36%). Black race has been associated with increased clearance of bedaquiline and M2 and lower concentrations of both as a result [ 13 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black race was much more prevalent in the PROBeX study compared with the phase II studies (82% vs 36%). Black race has been associated with increased clearance of bedaquiline and M2 and lower concentrations of both as a result [ 13 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to TB, clearance of bedaquiline was 52% faster in Africans using a population pharmacokinetic model [ 211 ], which may be due to Africans expressing significantly more CYP3A5 compared to other populations [ 212 ]. Although bedaquiline is metabolized by CYP3A4, substrate specificity frequently overlaps between CYP3A4 and CYP3A5.…”
Section: Polymorphism In Cyp Enzymes With Specific Focus On Antimalar...mentioning
confidence: 99%
“…The distributions of CYP3A5*1 (normal function) and CYP3A5*3 (nonfunctional) alleles are significant factors in the variability of tacrolimus response (immunosuppression during organ transplant). In a recent study among South Africans, Haas et al 9 reported that CYP3A5*3 was associated with slower bedaquiline clearance during TB treatment. Remarkably, the frequency of CYP3A5*3 in African populations (16-18%) is far lower than the *1 frequency (about 56%).…”
Section: Perspectives Pharmacogenetic Variation In Africamentioning
confidence: 99%
“…(b) The frequency distribution of selected actionable G6PD and CYP2D6 alleles across African populations. 7,9 Allele frequencies are indicated as relative percentages (%), but are not to scale. The illustrated genetic heterogeneity across Africa emphasizes that a single African population cannot proxy the entire continent in implementation of clinical pharmacogenomics.…”
Section: Challenges and Future Directions In Promoting Pharmacogenomi...mentioning
confidence: 99%
See 1 more Smart Citation